The effect of feed additive ethoxyquin on tilapia growth performance and potential secondary hazard to consumers - Shanjun Chen; Chong Wang; Yanan Liu; Zhigang Zhou; Linglin Fu; Yanbo Wang (Food Science and Human Wellness)
Ethoxyquin (EQ) is a widely used feed additives for aquaculture, but the potential hazard to fish and consumers are not fully understood. In this work, EQ was applied to tilapia fed with either high-fat or low-fat feed, and the changes in growth performance and intestinal barrier integrality of genetically improved farmed tilapia was observed. Additionally, the microbiota in the intestinal content and flesh was analyzed by 16S rDNA sequencing, and the flesh metabolites was measured by LC-MS/MS untargeted metabolomics. In the low-fat group, EQ increased weight gain and feed conversion rate, but reduced survival rate. In the high-fat group, only weight gain decreased, and there was no significant effect on feed conversion rate and survival rate. Additionally, the intestinal villi and microbiota diversity was impaired in both feeding conditions. Microbiota analysis revealed that EQ resulted in different composition and lower diversity of the flesh microbiota and upregulated the proportion of potential pathogens. EQ also changed the flesh metabolome, decreasing beneficial metabolites and increasing potential harmful components. This work elucidated the effect of EQ on growth performance of tilapia and implied that it has adverse effects on tilapia and may be passed on to consumers.